The role of technology in the fight against human trafficking: Reflections on privacy and data protection concerns. Issue 2 (April 2016) - Gerry QC, Felicity; Muraszkiewicz, Julia; Vavoula, Niovi
Abstract: Over the past decade, policy makers, academics and activists have looked into solutions within the realm of technology as a means of stepping up the fight against human trafficking while ensuring a high level of protection of the victims. Even though different types of technology might be effective in the context of crime prevention, investigation or prosecution (whether national or transnational) and victim protection, such processes inevitably raise significant concerns particularly in relation to privacy and data protection. This article aims to offer an introduction to these challenges in order to trigger a much-needed dialogue in this regard. After outlining key terms and main provisions concerning privacy and data protection, the present article then explores three ways in which technological developments can contribute to combatting human trafficking – location tracking, data collection and drones –, through these it highlights the respective privacy and data protection concerns and attempts to offer ways forward.